The influence of web-based projects on students digital creativity in physics education: a gender-based analysis - Kurniawan Arizona; Ramdhani Sucilestari; Rizal M. Suhardi (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to examine the effect of web-based project learning on physics students' digital creativity in the Physics Learning Innovation course, with a focus on gender differences. Using a factorial experimental design, the study involved 37 students and two factors: web-based project learning method and gender. Data were collected through a project-based performance assessment rubric that measured students' digital creativity in four aspects: fluency, flexibility, originality, and elaboration. The data were analyzed using a two-way ANOVA to examine the effects of the learning method, gender, and their interaction on students' digital creativity. The results indicated no statistically significant difference in students' digital creativity between web-based project learning in 2023 and 2024 (p>0.05). These findings suggest a consistent impact of the learning model across different cohorts. In terms of gender, the results revealed no significant difference in digital creativity between male and female students (p>0.05). The interaction between learning method and gender was not significant (p>0.05), indicating that they have independent effects. This research contributes to understanding the effectiveness of web-based learning to enhance digital creativity in physics education, as well as recommends wider application of this method in science and technology courses.